Pre-design guidelines for passive solar architectural buildings in Kenya - Rabah, Kefa V.O.; Mito, Collins O. (My University, 2003)
Analyses have been done on the climatic data to obtain physical building design specifications for various regional climatic conditions in Kenya. The main aim is to provide a general and appropriate information at strategic pre-design stages to make better use of passive solar energy in urban planning and, building design for better indoor 'comfort' climate and, the health and productivity of the building occupants. It utilizes a computer program, ARCHIPAK together with climatic data (for 8 year period) to get 'comfort zones', and 'control potential zones'(CPZs), for nine stations representing Kenya fairly well by virtue of their geographical locations. The use of the CPZs in building design and the objectives of the pre-design guidelines are discussed for eight major provincial urban centers and the capital City of Nairobi, all with distinctive climatic conditions. Opportunities and limitations of the pre-design guidelines are also discussed. © 2003 Taylor & Francis Ltd.
Keywords: Climatic design; Human comfort; Passive architecture; Solar energy; Thermal comfort